Comparative Efficacy of Florpyrauxifen-Benzyl, 2,4-D, and Penoxsulam on Water Hyacinth (Eichhornia crassipes [Mart.] Solms) - Denny Kurniadie; Muhammadiyah; Milwan Fatya Cholis; Pauline Elisabeth (UIN Sunan Gunung Djati Bandung, 2026)
Water hyacinth (Eichhornia crassipes [Mart.] Solms) is one of the most problematic invasive aquatic weeds, causing severe ecological and economic damage in tropical regions. Herbicides are often considered the most efficient approach for managing aquatic weeds compared to mechanical or biological control methods. However, conventional herbicides such as 2,4-dichlorophenoxyacetic acid (2,4-D) require high application rates and may pose environmental risks. Therefore, new herbicides with greater efficacy at lower doses and improved environmental safety are required. This study aimed to evaluate the effectiveness of florpyrauxifen-benzyl, a novel auxin-mimicking herbicide, compared with 2,4-D and penoxsulam in suppressing the growth of E. crassipes. The experiment was conducted from April to June 2022 under greenhouse and open-field conditions using a randomized complete block design with ten treatments, each with three replications, namely Florpyrauxifen-benzyl (FB, 10 g a.i./ha), Penoxsulam (P, 12.5 g a.i./ha), and 2,4-D (400 g a.i./ha). The parameters observed included phytotoxicity symptoms, water loss, dry weight, and damage percentage. The results revealed that florpyrauxifen-benzyl at 15–20 g a.i./ha provided growth suppression comparable to 2,4-D at 600 g a.i./ha, while penoxsulam exhibited lower efficacy. In conclusion, florpyrauxifen-benzyl demonstrates strong potential as a low-dose, environmentally safer, and sustainable herbicide for the management of water hyacinth under tropical conditions in Indonesia, offering practical benefits in reducing chemical inputs for aquatic weed control programs